2021
DOI: 10.3390/ijerph182312678
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Environmental Impacts of the Dairy and Baby Food Industries: Are First-Food Systems a Crucial Missing Part of the Healthy and Sustainable Food Systems Agenda Now Underway?

Abstract: Food systems are increasingly being understood as driving various health and ecological crises and their transformation is recognised as a key opportunity for planetary health. First-food systems represent an underexplored aspect of this transformation. Despite breastfeeding representing the optimal source of infant nutrition, use of commercial milk formula (CMF) is high and growing rapidly. In this review, we examine the impact of CMF use on planetary health, considering in particular its effects on climate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 100 publications
(174 reference statements)
0
32
0
1
Order By: Relevance
“…The largest producers are India, the European Union (EU) and the USA, at 196.2 million, 167.4 million and 99.2 million tons produced, respectively. The Organization for Economic Co-operation and Development (OECD) expects global annual milk production to reach 997 million tons by 2029 [ 3 , 4 ]. This growth in milk production goes hand in hand with the increased generation of wastewater, whose properties make it dangerous to aquatic ecosystems [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The largest producers are India, the European Union (EU) and the USA, at 196.2 million, 167.4 million and 99.2 million tons produced, respectively. The Organization for Economic Co-operation and Development (OECD) expects global annual milk production to reach 997 million tons by 2029 [ 3 , 4 ]. This growth in milk production goes hand in hand with the increased generation of wastewater, whose properties make it dangerous to aquatic ecosystems [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported increasing global sales of milk-based formulas intended for infants and young children [ 10 , 11 ]. Concerns have been raised around this increasing use of milk-based formulas, both in regards to health and economic, as well as social and environmental factors [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Awareness of food system sustainability is high on the global political agenda [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of food system sustainability is high on the global political agenda [ 17 , 18 ]. Numerous recent reports call for more sustainable food systems and diets [ 19 , 20 , 21 , 22 ], including those for infants and young children [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of those forced from their homes because of climate change live in developing countries, and women and children are amongst the most vulnerable to its consequences, with displaced women facing increased risk of gender‐based violence, including domestic violence, forced marriage and trafficking (CARE International, 2020 ). UN and government agendas, however, are not paying enough attention to the disproportionate impact that climate change has on the health and food and nutrition security of women, infants, and children living in low‐income settings (Blakstad & Smith, 2020 ; CARE International, 2020 ; Pope et al, 2021 ).…”
mentioning
confidence: 99%